A Compact RFID Reader Antenna for UHF Near-Field and Far-Field Operations - Lai Xiao zheng; Xie Zeming; Cen Xuanliang (International Journal of Antennas and Propagation)
A compact loop antenna is presented for mobile ultrahigh frequency (UHF) radio frequency identification (RFID) application. This antenna, printed on a 0.8 mm thick FR4 substrate with a small size of 31 mm × 31 mm, achieves good impedance bandwidth from 897 to 928 MHz, which covers USA RFID Band (902–928 MHz). The proposed loop configuration, with a split-ring resonator (SRR) coupled inside it, demonstrates strong and uniform magnetic field distribution in the near-field antenna region. Its linearly polarized radiation pattern provides available far-field gain. Finally, the reading capabilities of antenna are up to 56 mm for near-field and 1.05 m for far-field UHF RFID operations, respectively.